Venezuela and OPEC, fifty years later - Mommer, B (Oxford Institute for Energy Studies, 2011)
On 14 September 2010, OPEC celebrated its fiftieth birthday. Venezuela was one of five founding Members, together with Saudi Arabia, Iran, Iraq and Kuwait. But more than that, Venezuela, in the person of Juan Pablo Pérez Alfonzo, played a stellar role in setting up this organisation, at the side of Saudi Arabia, represented by Abdullah Al-Tariki. These two men shared one vision, centred on the question of the price of oil. This common vision was embodied in the OPEC Founding Resolution (14 September 1960), which speaks of nothing but prices. In order to stabilise them, that resolution suggests the regulation of production as a possible option. (The Venezuelan government formally ratified the OPEC treaty in May 1961.)